2022
DOI: 10.1038/s41598-021-04091-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cells isolated from epithelial cell rests of Malassez through single-cell limiting dilution

Abstract: The epithelial cell rests of Malassez (ERM) are essential in preventing ankylosis between the alveolar bone and the tooth (dentoalveolar ankylosis). Despite extensive research, the mechanism by which ERM cells suppress ankylosis remains uncertain; perhaps its varied population is to reason. Therefore, in this study, eighteen unique clones of ERM (CRUDE) were isolated using the single-cell limiting dilution and designated as ERM 1–18. qRT-PCR, ELISA, and western blot analyses revealed that ERM-2 and -3 had the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Both morphometric parameters suggest a reduced surface attachment and less cell stretching of the respective cells. However, for other cell cultures it has been reported that cellular morphology and growing behavior have been changed more drastically upon clonal isolation, although it was not interpreted as a result of single-cell isolation [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both morphometric parameters suggest a reduced surface attachment and less cell stretching of the respective cells. However, for other cell cultures it has been reported that cellular morphology and growing behavior have been changed more drastically upon clonal isolation, although it was not interpreted as a result of single-cell isolation [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Due to the statistical nature of obtaining a single cell after dilution, this clonal isolation method is comparatively inefficient and laborious [ 9 ]. However, due to its ease of use, it is still widely applied in the field of cell engineering [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%